Relación entre la aplicación de estrategias de enseñanza grupal y el aprendizaje de valores ecológicos en los alumnos del 2do grado de secundaria en el área de ciencia, tecnología y ambiente de las I.E del distrito de Rioja - Torres Cotrina, Rosbel Blademir (2012)
Gomez et al. (1993), indicate that among the fundamental objectives of group work as a teaching strategy is the strengthening and increased sense of responsibility, the capacity development of cooperation, strengthening communication skills, the revitalization of intellectual skills and professional and consequent facilitation of the growth process of the student and the teacher in the sense of becoming better human beings and citizens more and more. These advantages granted teamwork must be transformad into a set of criteria prevailing pedagogical work in schools in our district, since the intervention group appears to be safer and more effective than individual development, because by promoting the collaboration educational provísion is more effective in the analysis of problems that are common to all the possibilíty of better and multiple criteria. lt is in this context that teachers should address environmental issues so that, consistent with the overall needs of environmental education is to guide students toward making a strong awareness of the vital importance of the environment in which they live and the concern for their care is a daily practice. Our research was aimed at finding the possible relationship between the implementation of teaching strategies on the type of group work by teachers and student learning. as. the expr:ess.ion of em/.ir.onmental values, within the second degree of secondary education · educational institutions more representativa of the district of Rioja. The two key instruments for the assessment of the variables considerad in the study were: a closed questionnaire for teachers, through which the importance was found that these give the working group as a teaching strategy, the other was a test instrument with evaluativa type response scale to establish clear parameters in the emission of the response of the students about the ecological values learned Xlll On the side of teachers, the general trend of the results shows an adequate and acceptable for the application of group teaching strategies. While on the side of students, very significant values were obtained indicating the presence of values in the ecological dimension of learning that second graders are· achieving secondary school in the area of Science Technology and Environment. The relational indicators of the variables studied were inclined toward a highly significant trend of association. This presence bound in the teachinglearning process is how favorable they stress the planning and implementation of strategies for group work if it is to teach values and even more so considering that in ecological terms is necessary to encourage the cooperative participation of different social groups prese.n t in educational institutions in our district.